Increased MPO concentration but decreased peroxidase activity in saliva of obese women - Katarzyna Korybalska; Anna Surdacka; Anna Lehmann; Joanna Żuraszek-Szymańska; Janusz Witowski (Scientific Reports)
Abstract Myeloperoxidase (MPO) is a key element of host defense against pathogens but is also implicated in disease. To explore whether MPO contributes to the postulated relationship between oral inflammation and obesity, the concentration of MPO and its activity were studied in saliva of obese and non-obese individuals. Whole mixed unstimulated saliva was obtained from 44 apparently healthy women without (n = 25) and with (n = 19) simple obesity. MPO concentration in saliva was measured by immunoassay; salivary peroxidation and chlorination activities were assessed with tetramethylbenzidine- and aminophenyl-fluorescein-based assays, respectively. Salivary MPO concentrations were found to be significantly higher in obese than in non-obese women and could distinguish these two populations. However, it did not correlate with total salivary peroxidation activity (TSPA), which was lower in obese women. MPO chlorinating activity was not detected in pure saliva in neither of the groups. The subjects’ body weight, waist-to-hip ratio and the concentration of pro-inflammatory cytokines in saliva correlated positively with MPO concentration, but negatively with TSPA. In conclusion, MPO concentration in saliva is significantly increased in obesity but does not correlate with salivary peroxidation activity, which is lower in the obese. It may indicate that obesity impairs the ability of saliva to mitigate oxidative stress associated with inflammation.